Implementation of Flipped Classroom as an Innovative Learning Strategy to Increase Independence and Concept Understanding of MPI Study Program Students - Ma’arif, Mohamad Ahyar (LP3M Universitas Islam Zainul Hasan Genggong, 2025)
This study aims to examine the effectiveness of the Flipped Classroom learning model in improving learning independence and concept understanding of students of the Islamic Education Management (MPI) Study Program. The research used a quantitative approach with a pseudo-experimental method through a pretest-posttest control group design. The sample consisted of 50 students who were divided into two groups, 25 students in the experimental group and 25 students in the control group. The research instruments were concept understanding test and learning independence questionnaire. Data analysis used independent sample t-test, Wilcoxon, Mann-Whitney, and N-Gain analysis. The results showed a significant increase in students' concept understanding in the experimental group with an average posttest of 81.10 and an N-Gain score of 0.5269, compared to the control group which had an average value of 67.78 and N-Gain 0.2887. The t-test produced a p value = 0.000, indicating a significant difference. In terms of learning independence, there was an increase in indicators of initiative, time management, and independent responsibility. As many as 92% of experimental group students were in the medium category and 8% in the high category. These results confirm that Flipped Classroom is effective in the context of MPI learning which demands a reflective, independent, and technology-based approach.